MORPHOLOGICAL CHARACTERIZATION OF GLADIOLUS (GLADIOLUS X HYBRIDUS HORT.) FOR RESISTANCE TO FUSARIUM WILT DISEASE - POONAM KUMARI; T. MANJUNATHA RAO; RAJIV KUMAR; M. V. DHANANJAYA; R. VENUGOPALAN (The Bioscan, 2015)
Four gladiolus genotypes were evaluated under field conditions for vegetative and floral characters at ICAR-Indian Institute of Horticultural Research, Bengaluru during 2011- 2012. The results revealed that ‘Arka Amar’ and ‘Arka Aayush’ were resistant genotypes, whereas, ‘IIHRG-12’ and ‘Pink Friendship’ were susceptible to Fusarium wilt disease. The genotype ‘IIHRG-12’ took minimum number of days (53.44 days) to spike emergence and flowering (63.96 days). Among all the genotype tested genotype, ‘IIHRG-12’ recorded maximum plant height (137.76 cm), spike length (119.40 cm) and rachis length (51.92 cm). The genotype ‘Arka Amar’ was found superior for floret diameter (10.39 cm), number of florets per spike (16.52), number of marketable spikes per corm (2.44) and vase life (8.87 days). Genotype ‘Pink Friendship’ recorded the maximum spike weight (83.00 g). Based on results obtained, the genotypes ‘Arka Amar’ and ‘IIHRG-12’ can be utilized in breeding programs for improvement of vegetative and floral characters in gladiolus.